Dismissing negative stigma, embracing change: The BK teacher's role in supporting student development at SMK Mikael Surakarta - Sela Fajar Ariani (Priviet Social Sciences Journal, 2025)
This study aimed to analyze the role of Guidance and Counseling (BK) teachers in supporting student development and dismissing the negative stigma against BK services at SMK Mikael Surakarta. Descriptive qualitative research was used, and data collection techniques included observations, interviews, and documentation. The results showed that counseling teachers play a strategic role in helping students face academic, social, emotional, and career planning challenges. However, there is still a negative stigma among students who consider counseling services as a form of punishment rather than assistance. To overcome this, BK teachers apply a humanist approach, student need-based programs, and peer counselor empowerment to create more inclusive and supportive services. Thus, counseling services at SMK Mikael Surakarta not only function as a problem-solving space but also as an agent of change that plays a role in holistically developing students’ potential and character.